What has affected the governance effect of the whole population coverage of medical insurance in China in the past decade? Lessons for other countries - Zhang, Ting; Zhang, Hongyu; Miao, Wenqing; Xu, Jinpeng; Shi, Qi; Liu, Jian; Deng, Fangmin; He, Jingran; Chen, Fangting; Kang, Zheng; Wu, Qunhong; Tian, Guomei (Frontiers in Public Health, 2023)
Objective This study aimed to explore the current state of governance of full population coverage of health insurance in China and its influencing factors to provide empirical references for countries with similar social backgrounds as China. Methods A cross-sectional quantitative study was conducted nationwide between 22 January 2020 and 26 January 2020, with descriptive statistics, analysis of variance, and logistic regression models via SPSS 25.0 to analyze the effectiveness and influencing factors of the governance of full population coverage of health insurance in China. Results The effectiveness of the governance relating to the total population coverage of health insurance was rated as good by 59% of the survey respondents. According to the statistical results, the governance of the public's ability to participate in insurance (OR = 1.516), the degree of information construction in the medical insurance sector (OR = 2.345), the government's governance capacity (OR = 4.284), and completeness of the government's governance tools (OR = 1.370) were all positively correlated (p < 0.05) on the governance effect of the whole population coverage of health insurance. Conclusions The governance of Chinese health insurance relating to the total population coverage is effective. To effectively improve the effectiveness of the governance relating to the total population coverage of health insurance, health insurance information construction, governance capacity, and governance tools should be the focus of governance to further improve the accurate expansion of and increase the coverage of health insurance.